New features of the Blocks Database servers. - Henikoff, J G (1999)
Blocks are ungapped multiple sequence alignments representing conserved protein regions, and the Blocks Database consists of blocks from documented protein families. World Wide Web (http://www. blocks.fhcrc.org) and Email (blocks@blocks.fhcrc.org) servers provide tools for homology searching and for analyzing protein family relationships. New enhancements include a multiple alignment processor that extends the use of these tools to imported multiple alignments of families not present in the database and a PCR primer designer that implements a new strategy for gene isolation.